PERFIL DA MORTALIDADE POR CÂNCER DE MAMA NO BRASIL - PERÀODO DE 2010 A 2015 (CIPEEX, 2022)
ABSTRACTINTRODUCTION: CONSIDERED FOR ITS SEVERITY AND INTENSITY THE FIRST CAUSE OF CANCER DEATH AMONG WOMEN, WITH 522 THOUSAND DEATHS WORLDWIDE IN 2012, REPRESENTING 14.7% OF ALL DEATHS AND 14,388 DEATHS IN 181 CASES IN MEN. AND IN 2015, 15,403 DEATHS FROM BREAST CANCER ARE REPORTED IN BRAZIL. BREAST CANCER HAS RELATIVELY LOW LETHALITY, SINCE THE MORTALITY RATE IS LESS THAN ONE-THIRD OF THE INCIDENCE RATE (BRAZIL, 2017). OBJECTIVE: TO TRACE THE MORTALITY PROFILE IN BRAZIL, CENTRAL-WEST REGION AND GOIS, FROM 2010 TO 2015. METHODOLOGY: THIS IS A RETROSPECTIVE STUDY WITH A QUANTITATIVE APPROACH USING DATASUS SECONDARY DATA. THE DATA OF THE STUDY WERE OBTAINED BY CONSULTING THE FOLLOWING DATABASES OF THE SIM (MORTALITY INFORMATION SYSTEM), MADE AVAILABLE BY THE DEPARTMENT OF INFORMATICS OF THE UNIFIED HEALTH SYSTEM (DATASUS), SUPPORT ROOM FOR STRATEGIC MANAGEMENT OF THE MINISTRY OF HEALTH (SAGE) AND CANCER INSTITUTE (INCA), SCIENTIFIC AND MANUAL ARTICLES. DATA FROM PUBLIC OR SECONDARY DOMAIN WERE USED, AND IT WAS NOT NECESSARY TO SUBMIT TO THE RESEARCH ETHICS COMMITTEE. THE POPULATION OF THE STUDY CONSISTED OF DATA FROM BRAZILIAN WOMEN IN THE CENTER-WEST REGION OF GOIS, OBSERVING AND DESCRIBING THE PROPORTIONAL INCIDENCE OF BREAST CANCER IN RELATION TO THE TOTAL NUMBER OF DEATHS, USING DETERMINANTS SUCH AS AGE, COLOR, UNDERLYING CAUSE OF DEATH, RESIDENCE AND OCCURRENCE IN THE PERIOD FROM 2010 TO 2015. TO AVOID ERRORS OF DELAY IN THE NOTIFICATION, WE WILL ANALYZE THE AVAILABLE DATA UNTIL 2014, THE LAST YEAR IN WHICH THE COMPLETE DATA IS CONTAINED IN DATASUS. THE DATA COLLECTED WAS APPLIED TO THE MICROSOFT® EXCEL 2010 PROGRAM FOR TABULATION AND DESCRIPTIVE STATISTICAL ANALYSIS WITH ABSOLUTE AND RELATIVE FREQUENCY AND ARE PRESENTED THROUGH TABLES AND GRAPHS. RESULTS: THE HIGHEST MORTALITY RATES OCCURRED IN WOMEN AGED 50 TO 69 YEARS, BUT IT WAS POSSIBLE TO NOTICE A DECLINE FROM THE YEAR 2014 TO THE YEAR 2015. THE HIGHEST NUMBER OF DEATHS WAS ETHNIC / WHITE RACE FOLLOWED BY BLACKS, WHICH MAY BE JUSTIFIED BY THE BRAZILIAN POPULATION BEING LARGER CONSTITUTED BY THIS RACE. IN THE CENTRAL-WEST REGION, WHAT WAS HIGHLIGHTED WAS THE FEDERAL DISTRICT, BEING THE MOST PREVALENT IN THE NUMBER OF DEATHS EVEN MORE THAN IN BRAZIL. CONCLUSION: TODAY, ACCESS TO DIAGNOSIS AND TREATMENT IS EASIER, SINCE IT WAS THE CREATION AND DEVELOPMENT OF PUBLIC POLICIES OVER THE YEARS THAT PROVIDED IMPROVEMENTS AND CHANGES IN WOMEN'S HEALTH, NOTING THAT CURRENTLY THE INFORMATION CAN BE FOUND IN SEVERAL AREAS OF HEALTH , THERE IS STILL RESISTANCE BY MANY WOMEN TO TREATMENT, FOR FEAR OF A POSSIBLE MASTECTOMY, NOT FOR FAMILY SUPPORT, FOR CRITICISM OF SOCIETY. NURSING PLAYS A FUNDAMENTAL ROLE IN THE COORDINATION OF PREVENTION ACTIONS, IMPLEMENTING HEALTH EDUCATION STRATEGIES
Keywords: Breast Neoplasms. Mortality of Breast Cancer. Public policy